Higher order sliding mode controller design for a research nuclear reactor considering the effect of xenon concentration during load following operation. (January 2015) - Ansarifar, G.R.; Rafiei, M.
Highlights: Higher order Sliding Mode Control system has been presented for core power control. The reactor core has been simulated based on the point kinetics equations. The model assumes feedback from lumped fuel and coolant temperatures. The effect of xenon concentration was also included. The control system is guaranteed to be stable within a large range. Abstract: Reactor power control is one of the most important problems in a nuclear power plant. This paper presents the higher order sliding mode controller (H.O.S.M.C.) which is a robust nonlinear controller for a nuclear research reactor considering the effect of xenon concentration during load following operation. Sliding mode controllers for nuclear reactors were developed before. Traditional sliding mode technique has intrinsic problem of chattering. To cope with this problem higher order sliding mode (HOSM) is used. The nonlinear model of a research reactor (Pakistan Research Reactor-1) has been used for higher order sliding mode controller design and performance evaluation. The reactor core is simulated based on the point kinetics equations and three delayed neutron groups. The model assumes feedback from lumped fuel and coolant temperatures. The effect of xenon concentration is also included. The employed method is easy to implement in practical applications and moreover, the higher order sliding mode control exhibits the desired dynamic behavior during the entire output-tracking process. Simulation results show the effectiveness of the proposed controller in terms of performance, stability and robustness against disturbances.